P.02 The Alien Limb Syndrome of corticobasal degeneration is both common and independent of apraxia. Issue 9 (7th August 2011) - Lewis-Smith, D J; Ghosh, B C P; Rowe, J B
Abstract : Introduction: Patients with corticobasal degeneration (CBD) have well known difficulties in praxis and may experience alien limb phenomena (ALP). While cases of alien limb syndrome (ALS) with vascular or surgical aetiologies have received much attention, less is understood about ALS in CBD despite this being a diagnostic criterion. The ALS of CBD has been interpreted as a deficit in praxis. This study sought to establish whether this assumption is justified. Methods: We reviewed the cases of 30 patients with CBD and 25 with the closely related tauopathy progressive supranuclear palsy (PSP) at a specialist neurology clinic. Consultations included a structured examination of praxis and 14 questions designed to elicit symptoms of ALS. Quantitative scores were allocated to each examination and questionnaire. Results: 83% of CBD patients reported at least one possible ALP, 57% reported more than four. Only one PSP patient reported any ALP. Commonly reported ALP included spontaneous limb levitation (50%), the sense that the patient's hand did not belong to them (50%), and reaching for objects against the patient's will (30%). CBD patients with ALS rarely experienced a delusion of external control (17%). Importantly, no correlation was found between limb praxis and alien limb questionnaire scores among CBD patients (r=0.04, ns). Conclusions: Symptoms of ALS are common in CBD, but do not occur in PSP. Our results cast doubt on the assumption that ALS in CBD is a manifestation of severe apraxia.